A study on the financial performance between takaful insurance and conventional insurance in Malaysia / Norlina Mohd Yazid - Mohd Yazid, Norlina (Faculty of Business and Management, 2011)
This research paper will study about the financial performance of takaful insurance and insurance in Malaysia. The main aim of this study is to examine the financial performance of insurance as well as takaful insurance. Other than that, this paper study will also compare the financial performance between takaful and insurance in order to determine which insurance industry has a better financial performance in Malaysia. The main data collection from the annual financial reports on Prudential Assurance Malaysia Berhad and Prudential BSN Takaful Berhad in 2007 to 2009. Different financial ratio are evaluated such as return on assets, return on deposits, profit margin, assets utilization, operating efficiency ratio, interest/investment margin and finally measure the best performance between two insurance companies from 2007 to 2009. It is most important factors for performance evaluation. The graphical analysis and comparisons are applies between two companies for measurement of all types of financial ratio analysis.